Pengaruh Arus Kas Operasional dan Laba Bersih terhadap Harga Saham pada Perusahaan Subsektor Perkebunan yang Terdaftar di Bursa Efek Indonesia Periode 2020–2024 - Putri Nadillah; Irwansyah Aditya Saputra (AKUNTANSI 45, 2026)
This study aims to analyze the effect of operating cash flow and net income on stock prices in plantation subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The independent variables in this research are operating cash flow and net income, while the dependent variable is stock price. The research method employed is a quantitative approach with multiple linear regression analysis. The research sample was determined using purposive sampling, resulting in seven plantation subsector companies as the objects of the study. The data used consist of annual financial statements and year-end closing stock price data. The results of the study indicate that, partially, operating cash flow has no significant effect on stock prices, and net income also has no significant effect on stock prices. Simultaneously, operating cash flow and net income do not have a significant influence on stock prices. The relatively low coefficient of determination (R²) suggests that stock prices are largely affected by other factors not examined in this study, such as macroeconomic conditions, fluctuations in plantation commodity prices, government policies, and market sentiment. Based on these findings, it can be concluded that operating cash flow and net income are not the primary factors influencing stock prices of plantation subsector companies during the study period. The implication of this research is that investors should consider external factors beyond the company’s fundamental performance when making investment decisions.